2021
DOI: 10.1155/2021/1148954
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Optimization of Data Mining and Analysis System for Chinese Language Teaching Based on Convolutional Neural Network

Abstract: Chinese language is also an important way to understand Chinese culture and an important carrier to inherit and carry forward Chinese traditional culture. Chinese language teaching is an important way to inherit and develop Chinese language. Therefore, in the era of big data, data mining and analysis of Chinese language teaching can effectively sum up experience and draw lessons, so as to improve the quality of Chinese language teaching and promote Chinese language culture. Text clustering technology can analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that the proposed strategy provides more accurate learning improvement than the current method. The existing methodologies like CNN [23], SVM [24] and KNN [25]. With the suggested system, accuracy is at 93%, while CNN is at 75%, SVM is at 63%, and KNN is at 82%.…”
Section: Accuracymentioning
confidence: 96%
See 1 more Smart Citation
“…It has been demonstrated that the proposed strategy provides more accurate learning improvement than the current method. The existing methodologies like CNN [23], SVM [24] and KNN [25]. With the suggested system, accuracy is at 93%, while CNN is at 75%, SVM is at 63%, and KNN is at 82%.…”
Section: Accuracymentioning
confidence: 96%
“…The article presents several forms of educational materials and shows how they may be used to enhance learning services [21] [22].The research explained about building the text clustering approach using convolutional neural networks may more effectively and thoroughly mine. Chinese character data led to the optimization of the k-means method to reach the desired accuracy [23]. The article developed the strength of the social and educational sectors involved with the standard of art education, as well as artistic potential.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%